An Empirical Investigation of the Cash Conversion Cycle of Small Business Firms - Katerina Lyroudi; Dan McCarty (Journal of Small Business Finance, 1993)
The purpose of this study is to examine the cash conversion cycle as an indicator of the company's liquidity, to determine the relationship of the cash conversion cycle with the current and the quick ratios and with its component variables, and to investigate the implications of the cash conversion cycle for small businesses in terms of profitability and firm size.
Keywords: L25; G32; 650; Cash Conversion Cycle; CCC; Small Business; Small Firm